Powder sintering type tantalum electrolytic capacitor anode and preparation method thereof

By covering the tantalum powder surface of the tantalum electrolytic capacitor with high dielectric constant substances and sintering and empowering treatment, the thermal runaway problem and large volume of the tantalum electrolytic capacitor in high voltage or high current applications is solved, and the improvement of the electrostatic capacity and voltage resistance performance and the miniaturization of the device are achieved.

CN119626781AActive Publication Date: 2025-03-14XI AN JIAOTONG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411751942.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-14
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Tantalum electrolytic capacitors are prone to thermal runaway or ignition when applied at high voltage or high current, and their size is large, making it difficult to meet the electronics industry's demand for miniaturization.

Method used

By covering the surface of the tantalum powder with high dielectric constant substances, sintering and empowering treatment, a block anode for a high dielectric composite tantalum electrolytic capacitor is formed, which increases the dielectric constant of the composite dielectric layer, increases the electrostatic capacity, and alleviates the device failure problem caused by crystallization.

Benefits of technology

It effectively improves the electrostatic capacity and voltage resistance of tantalum electrolytic capacitors, reduces the device volume, suppresses crystallization, and extends the device service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119626781A_ABST
    Figure CN119626781A_ABST
Patent Text Reader

Abstract

The invention discloses a powder sintering type tantalum electrolytic capacitor anode and a preparation method thereof, and belongs to the technical field of tantalum electrolytic capacitors. The preparation method of the anode of the powder sintering type tantalum electrolytic capacitor comprises the following steps: coating tantalum powder with a dielectric substance to obtain dielectric substance coated tantalum powder; the dielectric constant of the dielectric substance is greater than that of tantalum pentoxide; uniformly mixing the dielectric substance coated tantalum powder, a binder and a solvent to obtain slurry, and drying the slurry to remove the solvent to obtain mixed powder; and after the mixed powder is subjected to briquetting and shaping, degreasing treatment is carried out, then sintering is carried out in an oxygen-free atmosphere, and after sintering is completed, the powder sintering type tantalum electrolytic capacitor anode is obtained through energizing. According to the tantalum electrolytic capacitor, the high-dielectric-constant substance is introduced into the tantalum electrolytic capacitor, the dielectric constant of the composite dielectric layer is increased, the electrostatic capacity of the composite dielectric layer is effectively improved, and the problem of device failure caused by the crystallization phenomenon of the dielectric layer in the preparation process of the tantalum electrolytic capacitor powder accumulation sintering block is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of tantalum electrolytic capacitors, and more specifically to a powder sintered tantalum electrolytic capacitor anode and a preparation method thereof. Background Art

[0002] Capacitors play important roles in circuits such as filtering, rectification, coupling, decoupling, and bypassing. Large-capacity electrolytic capacitors have the ability to store electricity, charge and discharge, and allow DC power to be cut off through AC resistance. Aluminum electrolytic capacitors are generally used in consumer electronics, household appliances, industrial control, and other fields due to their low price, high rated withstand voltage, and ability to be used at lower frequencies. However, aluminum electrolytic capacitors have a short lifespan, are prone to aging, and their reliability decreases year by year. They are greatly affected by the environment, and their lifespan is halved for every 10°C increase in temperature. If they are not used for a long time and the rated voltage is suddenly applied, it is easy to cause the electrolytic capacitor to fail, be damaged, or even explode.

[0003] Tantalum electrolytic capacitors have high energy density, long life, high insulation resistance, low leakage current, wide operating temperature range, and high reliability. They are widely used in military communications, aerospace, industrial control, film and television equipment, communication instruments and other fields. With the continuous development of modularization and integration of equipment and instruments, the requirements for miniaturization of electronic components are getting higher and higher, and it is urgent to reduce the size of tantalum electrolytic capacitors. Tantalum electrolytic capacitors have limited voltage and current resistance. When high voltage or high current is used, it is easy to cause thermal runaway or fire, which hinders the development of the electronics industry. The essential reason is that the failure mechanism of tantalum electrolytic capacitors is largely because the oxide crystal defects in the dielectric weaken the amorphous dielectric and provide a conductive channel, which causes the positive and negative poles of the tantalum electrolytic capacitor to short-circuit, resulting in thermal runaway or fire. Summary of the invention

[0004] In view of the above problems, the present invention provides a powder sintered tantalum electrolytic capacitor anode and a preparation method thereof. In view of improving the electrostatic capacity of the block anode for tantalum electrolytic capacitors, reducing the volume of tantalum electrolytic capacitors, and solving the problem that the dielectric cannot be used for high voltage or high current due to the serious crystallization phenomenon during the energizing process, the present invention proposes coating the surface of tantalum powder with a high dielectric constant material, and forming a high dielectric composite tantalum electrolytic capacitor block anode after sintering and energizing. The introduction of high dielectric constant materials into tantalum electrolytic capacitors increases the dielectric constant of the composite dielectric layer, effectively improves its electrostatic capacity, and alleviates the device failure problem caused by the crystallization phenomenon of the dielectric layer during the preparation process of the sintered block of tantalum electrolytic capacitor powder.

[0005] A method for preparing a powder sintered tantalum electrolytic capacitor anode comprises the following steps:

[0006] The tantalum powder is coated with a dielectric material to obtain tantalum powder coated with a dielectric material; the dielectric constant of the dielectric material is greater than the dielectric constant of tantalum pentoxide;

[0007] The dielectric material is wrapped with tantalum powder, a binder and a solvent and mixed evenly to obtain a slurry, and the slurry is dried to remove the solvent to obtain a mixed powder;

[0008] After the mixed powder is pressed into a block, it is degreased at 100°C to 550°C, and then sintered at 1200°C to 2000°C in an oxygen-free atmosphere to obtain a powder sintered tantalum block. Then, after energization, a powder sintered tantalum electrolytic capacitor block anode is obtained.

[0009] For example, the degreasing temperature is 100°C, 130°C, 150°C, 190°C, 210°C, 250°C, 290°C, 310°C, 350°C, 390°C, 410°C, 450°C, 490°C, 510°C, 550°C, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0010] The sintering temperature is 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, 1700°C, 1800°C, 1900°C, 2000°C, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0011] In a preferred embodiment of the present invention, the slurry is composed of the following components in mass percentage: 40% to 80% of tantalum powder wrapped in dielectric material, 0.1% to 10% of binder, and the rest is solvent, which totals 100%. For example, the proportion of tantalum powder wrapped in dielectric material is 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, etc., and the proportion of binder is 0.1%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, etc. The proportion of solvent is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 59.9%, etc. However, it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0012] In a preferred embodiment of the present invention, the heating rate of degreasing is 5°C / min to 10°C / min, and the reaction time is 10min to 120min. For example, the degreasing time is 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable.

[0013] In a preferred embodiment of the present invention, the heating rate of sintering is 5°C / min to 10°C / min, and the reaction time is 10min to 120min. For example, the sintering time is 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min, etc., but it is not limited to the listed values, and other values ​​not listed in the above numerical range are also applicable. The sintering atmosphere is any one or more of a vacuum atmosphere, an argon atmosphere, a nitrogen atmosphere, and a hydrogen atmosphere.

[0014] In a preferred embodiment of the present invention, the dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum nitride, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate and bismuth ferrite. The particle size of the dielectric material is 0.1 nm to 500 nm.

[0015] In a preferred embodiment of the present invention, the specific capacitance of tantalum powder is 1000μF·V / g to 150000μF·V / g. For example, the specific capacitance of tantalum powder is 1000μF·V / g, 3000μF·V / g, 9000μF·V / g, 10000μF·V / g, 30000μF·V / g, 50000μF·V / g, 90000μF·V / g, 110000μF·V / g, 130000μF·V / g, 150000μF·V / g, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are equally applicable.

[0016] In a preferred embodiment of the present invention, the binder is one or more of polyvinyl alcohol, urea, polymethyl methacrylate, methyl methacrylate, polystyrene, polyvinyl chloride, stearic acid, glycerol, polyethylene glycol, paraffin, camphor, menthol, benzoic acid, polyethylene oxide, hydroxypropyl cellulose, acrylic resin, polypropylene carbonate, polyvinyl butyral and propylene carbonate.

[0017] The dispersant is water, methanol, ethanol, pineol, acetonitrile, acetone, dimethylformamide, N-methylpyrrolidone, n-butanol or methyl ethyl ketone.

[0018] During drying, the temperature may be 50-200° C., and the drying atmosphere may be any one or more of a vacuum atmosphere, an air atmosphere, an argon atmosphere, and a nitrogen atmosphere.

[0019] In a preferred embodiment of the present invention, in the briquetting step, the compaction density is 5 g / cm 3 ~10g / cm 3 For example, the compacted density is 5g / cm 3 , 6g / cm 3 , 7g / cm3 , 8g / cm 3 , 9g / cm 3 , 10g / cm 3 The above numerical range is not limited to the above numerical values, and other numerical values ​​not listed are also applicable.

[0020] In a preferred embodiment of the present invention, the coating method is liquid phase impregnation coating, vapor phase deposition coating or solid mixed coating. Furthermore, the vapor phase coating method is chemical vapor method, atomic layer deposition, molecular layer deposition, fluidized bed method, magnetron sputtering method; the liquid phase coating method is sol-gel method; the solid mixed coating method is to dry mix or wet mix tantalum powder with nano-scale high dielectric constant powder.

[0021] The second object of the present invention is to provide a powder sintered tantalum electrolytic capacitor anode prepared by the above preparation method.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention uses tantalum powder wrapped with dielectric material as raw material, and after the introduction of dielectric material, it undergoes subsequent high temperature and energizing treatment. The introduction of dielectric material effectively prevents local overheating and excessive local current, can effectively alleviate the crystallization phenomenon of tantalum pentoxide, and can effectively improve the dielectric constant of the block anode. Therefore, the introduction of dielectric material into the sintered block of tantalum electrolytic capacitor powder can not only increase the electrostatic capacitance of the anode foil and reduce the volume of the tantalum electrolytic capacitor, but also alleviate the device failure problem caused by the crystallization phenomenon of the dielectric layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Schematic diagram of sintering of solid mixed coated tantalum powder.

[0025] Figure 2 Schematic diagram of ALD vapor phase coating of tantalum powder.

[0026] Figure 3 This is a diagram of tantalum powder accumulation during sintering.

[0027] Reference numerals: 1-aluminum powder, 2-dielectric substance. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The failure mechanism of tantalum electrolytic capacitors is largely because the oxide crystal defects in the dielectric weaken the amorphous dielectric, providing a conductive channel, which causes the positive and negative electrodes of the tantalum electrolytic capacitor to short-circuit, resulting in thermal runaway or fire. The tantalum anodic oxide film (Ta2O5) formed by empowerment is an amorphous structure, but due to local overheating and excessive local current (due to oxide film defects, such as flaws and cracks), it provides activation energy for the reaction, drives the ions across the potential barrier and reorders them, and transforms from amorphous to crystalline phase structure. Based on this, the present invention introduces dielectric doping when preparing a bulk anode for tantalum electrolytic capacitors, and forms a high-dielectric composite dielectric layer after high-temperature heat treatment and empowerment, thereby increasing the dielectric constant of the composite dielectric layer, effectively improving its electrostatic capacitance, and alleviating the device failure problem caused by the crystallization phenomenon of the dielectric layer in the preparation process of the tantalum electrolytic capacitor powder accumulation sintered block.

[0030] The specific technical solutions are as follows:

[0031] Tantalum powder is coated with a dielectric material to obtain tantalum powder coated with a dielectric material; it is understandable that the thickness of the dielectric constant material coating is 0.1 to 30 nm.

[0032] Tantalum powder wrapped with dielectric material, a binder and a solvent are mixed evenly to obtain a slurry, and the slurry is dried to remove the solvent to obtain a mixed powder.

[0033] After the mixed powder block is formed, it is degreased at 100°C to 450°C, and then heated to 1200°C to 2000°C for sintering to produce micro-melting, thereby obtaining a powder sintered tantalum block. It should be noted that the powder sintered tantalum block prepared by the preparation method of the present invention is a high dielectric powder sintered tantalum block formed by wrapping tantalum powder with a high dielectric material.

[0034] During the shaping process of the compaction block, if the compaction density is too high, the tantalum powder will be deformed, while if the compaction density is too low, it will be difficult to shape.

[0035] During the degreasing process, if the degreasing temperature is too low, the binder will be carbonized, resulting in an increase in leakage current. If the degreasing temperature is too high, a thermal oxide film will be generated. If the thermal oxide film is too thick, the electrostatic capacitance will decrease.

[0036] During the sintering process, if the sintering temperature is too low, powder loss will occur. If the sintering temperature is too high, the specific surface area will be reduced, resulting in a decrease in electrostatic capacitance.

[0037] If a small amount of dielectric material is introduced, the improvement effect is not obvious, and a large amount of introduction will affect sintering.

[0038] Example 1

[0039] (1) Tantalum powder with a specific capacitance of 8000 μF·V / g and a purity of 99.95% and barium titanate with a particle size of 2 nm were uniformly mixed in a mass ratio of 95:5 to obtain dielectric material-coated tantalum powder.

[0040] (2) Weigh 65% of dielectric material-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0041] (3) Drying the slurry prepared in step (2) at 80° C. in air for 30 min to obtain a mixed powder.

[0042] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 7 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0043] (5) The block prepared in step (4) is degreased in an air atmosphere at 130° C. for 1 hour, and sintered in a vacuum atmosphere at 1400° C. for 30 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0044] Comparative Example 1

[0045] (1) Tantalum powder with a specific volume of 8000 μF·V / g and a purity of 99.95%, camphor, and anhydrous ethanol were uniformly mixed in a mass ratio of 65:5:30 to obtain a slurry.

[0046] (2) The slurry prepared in step (1) was dried at 80° C. in an air atmosphere for 30 min to obtain a mixed powder.

[0047] (3) The mixed powder prepared in step (2) is pressed into a block in a mold to a compacted density of 7 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0048] (4) The block prepared in step (3) is heated to 130°C at a heating rate of 10°C and degreased in an air atmosphere for 1 hour, and then heated to 1400°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 30 minutes to obtain a sintered block for tantalum electrolytic capacitors.

[0049] Example 2

[0050] (1) Tantalum powder with a specific capacitance of 50000 μF·V / g and a purity of 99.95% and barium titanate with a particle size of 2 nm were uniformly mixed in a mass ratio of 95:5 to obtain dielectric material-coated tantalum powder.

[0051] (2) Weigh 65% of dielectric substance-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0052] (3) The slurry prepared in step (2) was dried at 80° C. in an air atmosphere for 30 min to obtain a mixed powder.

[0053] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 7 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0054] (5) The block prepared in step (4) is heated to 130° C. at a heating rate of 10° C. and degreased in an air atmosphere for 1 h, and then heated to 1400° C. at a heating rate of 10° C. and sintered in a vacuum atmosphere for 30 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0055] Comparative Example 2

[0056] (1) Tantalum powder with a specific volume of 50000 μF·V / g and a purity of 99.95%, camphor and anhydrous ethanol were uniformly mixed in a mass ratio of 65:5:30 to obtain a slurry.

[0057] (2) The slurry prepared in step (1) was dried at 80° C. in an air atmosphere for 30 min to obtain a mixed powder.

[0058] (3) The mixed powder prepared in step (2) was pressed into a block in a mold to a compacted density of 4.9 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0059] (4) The block prepared in step (3) is heated to 130°C at a heating rate of 10°C and degreased in an air atmosphere for 1 hour, and then heated to 1400°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 30 minutes to obtain a sintered block for tantalum electrolytic capacitors.

[0060] Example 3

[0061] (1) Tantalum powder with a specific volume of 8000 μF·V / g and a purity of 99.95% was placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and isopropyl titanate as the titanium source. The temperature of the titanium source was maintained at 25°C. The powder was introduced for 5 seconds, and then nitrogen was introduced for 30 seconds. O3 was then introduced for reaction for 10 seconds, and then nitrogen was introduced for 50 seconds. The above steps were repeated for 200 times to obtain tantalum powder coated with dielectric material.

[0062] (2) Weigh 65% of dielectric material-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0063] (3) Drying the slurry prepared in step (2) at 80° C. in air for 30 min to obtain a mixed powder.

[0064] (4) The mixed powder prepared in step (3) is pressed into a block in a special mold to a compact density of 4.9 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0065] (5) The block prepared in step (4) is heated to 130° C. at a heating rate of 10° C. and degreased in an air atmosphere for 1 h, and then heated to 1400° C. at a heating rate of 10° C. and sintered in a vacuum atmosphere for 30 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0066] Example 4

[0067] (1) Tantalum powder with a specific volume of 8000 μF·V / g and a purity of 99.95% was placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5 mTorr, with nitrogen as the carrier gas and isopropyl titanate as the titanium source. The temperature of the titanium source was maintained at 25°C. The powder was introduced for 5 seconds, and then nitrogen was introduced for 30 seconds. O3 was then introduced for reaction for 10 seconds, and then nitrogen was introduced for 50 seconds. The above steps were repeated to deposit a thickness of 5 nm to obtain dielectric material-encapsulated tantalum powder.

[0068] (2) Weigh 65% of dielectric material-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0069] (3) Drying the slurry prepared in step (2) at 80° C. in air for 30 min to obtain a mixed powder.

[0070] (4) The mixed powder prepared in step (3) is pressed into a block in a special mold to a compact density of 4.9 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0071] (5) The block prepared in step (4) is heated to 130° C. at a heating rate of 10° C. and degreased in an air atmosphere for 1 h, and then heated to 1400° C. at a heating rate of 10° C. and sintered in a vacuum atmosphere for 30 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0072] Example 5

[0073] (1) Tantalum powder with a specific volume of 50000μF·V / g and a purity of 99.95% was placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5mTorr, with nitrogen as the carrier gas and isopropyl titanate as the titanium source. The temperature of the titanium source was maintained at 25°C. The reaction was continued for 5 seconds, and then nitrogen was passed in for 30 seconds. O3 was then passed in for reaction for 10 seconds, and then nitrogen was passed in for 50 seconds. The above steps were repeated for deposition, and the deposition thickness was 2nm to obtain tantalum powder wrapped with dielectric material.

[0074] (2) Weigh 65% of dielectric material-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0075] (3) The slurry prepared in step (2) was dried at 80° C. in an air atmosphere for 30 min to obtain a mixed powder.

[0076] (4) The mixed powder prepared in step (3) is pressed into a block in a special mold to a compact density of 4.9 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0077] (5) The block prepared in step (4) is heated to 130° C. at a heating rate of 10° C. and degreased in an air atmosphere for 1 h, and then heated to 1400° C. at a heating rate of 10° C. and sintered in a vacuum atmosphere for 30 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0078] Example 6

[0079] (1) Tantalum powder with a specific volume of 50000μF·V / g and a purity of 99.95% was placed in an ALD reaction chamber at a temperature of 200°C and a vacuum degree of 5mTorr, with nitrogen as the carrier gas and isopropyl titanate as the titanium source. The temperature of the titanium source was maintained at 25°C. The chamber was introduced for 5 seconds, and then nitrogen was introduced for 30 seconds. O3 was then introduced for reaction for 10 seconds, and then nitrogen was introduced for 50 seconds. The above steps were repeated for deposition, and the deposition thickness was 5nm to obtain tantalum powder coated with dielectric material.

[0080] (2) Weigh 65% of dielectric material-coated tantalum powder, 5% of camphor and 30% of anhydrous ethanol according to mass percentage and mix them evenly to obtain a slurry.

[0081] (3) The slurry prepared in step (2) was dried at 80° C. in an air atmosphere for 30 min to obtain a mixed powder.

[0082] (4) The mixed powder prepared in step (3) is pressed into a block in a special mold to a compact density of 4.9 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0083] (5) The block prepared in step (4) is heated to 130° C. at a heating rate of 10° C. and degreased in an air atmosphere for 1 h, and then heated to 1400° C. at a heating rate of 10° C. and sintered in a vacuum atmosphere for 30 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0084] Example 7

[0085] (1) Tantalum powder with a specific capacitance of 150,000 μF·V / g and a purity of 99.95% and tantalum nitride with a particle size of 2 nm are uniformly mixed in a mass ratio of 80:20 to obtain dielectric material-coated tantalum powder.

[0086] (2) Weigh 40% of tantalum powder coated with a dielectric material, 10% of urea and 50% of acetone according to mass percentage and mix them evenly to obtain a slurry.

[0087] (3) Dry the slurry prepared in step (2) at 200° C. in an argon atmosphere for 20 min to obtain a mixed powder.

[0088] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0089] (5) The block prepared in step (4) is heated to 450°C at a heating rate of 10°C and degreased in an air atmosphere for 10 minutes, and then heated to 1200°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 120 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0090] Example 8

[0091] (1) Tantalum powder with a specific capacitance of 30000 μF·V / g and a purity of 99.95% and niobium oxide with a particle size of 2 nm were uniformly mixed in a mass ratio of 70:30 to obtain dielectric material-coated tantalum powder.

[0092] (2) 40% of tantalum powder coated with a dielectric material, 10% of a composite binder and 50% of n-butanol were weighed and mixed evenly according to mass percentage to obtain a slurry, wherein the composite binder was a mixture of polyethylene glycol and polyvinyl alcohol in a mass ratio of 2:3, the molecular weight of the polyethylene glycol was 4000, and the molecular weight of the polyvinyl alcohol was 120000.

[0093] (3) Dry the slurry prepared in step (2) at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0094] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm2 .

[0095] (5) The block prepared in step (4) is heated to 250°C at a heating rate of 10°C and degreased in an air atmosphere for 50 minutes, and then heated to 2000°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 10 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0096] Example 9

[0097] (1) Tantalum powder with a specific capacitance of 30000 μF·V / g and a purity of 99.95% and barium strontium titanate with a particle size of 30 nm were uniformly mixed in a mass ratio of 70:30 to obtain dielectric material-coated tantalum powder.

[0098] (2) 80% of dielectric material-coated tantalum powder, 10% of composite binder and 10% of water were weighed and mixed evenly according to mass percentage to obtain a slurry, wherein the composite binder was urea, stearic acid and glycerol mixed in a mass ratio of 2:3.

[0099] (3) Dry the slurry prepared in step (2) at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0100] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 2 mm and an area of ​​2 cm 2 .

[0101] (5) The block prepared in step (4) is heated to 250°C at a heating rate of 10°C and degreased in an air atmosphere for 50 minutes, and then heated to 1800°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 15 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0102] Example 10

[0103] (1) Tantalum powder with a specific capacitance of 30000 μF·V / g and a purity of 99.95% and barium strontium titanate with a particle size of 0.1 nm are uniformly mixed in a mass ratio of 80:20 to obtain dielectric material-coated tantalum powder.

[0104] (2) According to the mass percentage, 40% of tantalum powder coated with dielectric material, 0.1% of composite binder and 59.9% of methanol are weighed and mixed evenly to obtain a slurry, wherein the composite binder is polystyrene and polyvinyl chloride mixed in a mass ratio of 2:3, the molecular weight of polystyrene is 60000, and the molecular weight of polyvinyl chloride is 100000.

[0105] (3) The slurry prepared in step (2) was dried at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0106] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0107] (5) The block prepared in step (4) is heated to 550° C. at a heating rate of 5° C. and degreased in an air atmosphere for 50 min, and then heated to 1500° C. at a heating rate of 5° C. and sintered in an argon atmosphere for 50 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0108] Embodiment 11

[0109] (1) Tantalum powder with a specific capacitance of 5000 μF·V / g and a purity of 99.95% and barium strontium titanate with a particle size of 2 nm are uniformly mixed in a mass ratio of 80:20 to obtain dielectric material-coated tantalum powder.

[0110] (2) 40% of dielectric material-coated tantalum powder, 0.1% of composite binder and 59.9% of N-methylpyrrolidone were weighed and mixed evenly according to mass percentage to obtain a slurry, wherein the composite binder was paraffin, menthol and benzoic acid mixed in a mass ratio of 1:1:1.

[0111] (3) The slurry prepared in step (2) was dried at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0112] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​3 cm 2 .

[0113] (5) The block prepared in step (4) is heated to 130°C at a heating rate of 10°C and degreased in an air atmosphere for 120 minutes, and then heated to 2000°C at a heating rate of 10°C and sintered in a vacuum atmosphere for 10 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0114] Example 12

[0115] (1) Tantalum powder with a specific capacitance of 5000 μF·V / g and a purity of 99.95% and lead zirconate titanate with a particle size of 6 nm are uniformly mixed in a mass ratio of 80:20 to obtain dielectric material-coated tantalum powder.

[0116] (2) 55% of dielectric material-coated tantalum powder, 5% of composite binder and 40% of pineol are weighed and mixed uniformly according to mass percentage to obtain a slurry, wherein the composite binder is polyethylene oxide, hydroxypropyl cellulose and acrylic resin mixed in a mass ratio of 2:2:1, the molecular weight of polyethylene oxide is 10,000, the molecular weight of hydroxypropyl cellulose is 40,000, and the molecular weight of acrylic resin is 80,000.

[0117] (3) The slurry prepared in step (2) was dried at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0118] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 8 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0119] (5) The block prepared in step (4) is heated to 450° C. at a heating rate of 8° C. and degreased in an air atmosphere for 10 min, and then heated to 2000° C. at a heating rate of 8° C. and sintered in a vacuum atmosphere for 10 min to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0120] Example 13

[0121] (1) Tantalum powder with a specific capacitance of 5000 μF·V / g and a purity of 99.95% is uniformly mixed with a dielectric material in a mass ratio of 80:20 to obtain tantalum powder coated with a dielectric material, wherein the dielectric material is a mixture of niobium oxide and hafnium oxide in a mass ratio of 1:1.

[0122] (2) 50% of dielectric material-coated tantalum powder, 10% of composite binder and 40% of acetonitrile were weighed and mixed uniformly according to mass percentage to obtain a slurry, wherein the composite binder is polymethyl methacrylate, polypropylene carbonate and polyvinyl butyral mixed in a mass ratio of 2:2:1, the molecular weight of polymethyl methacrylate is 100,000, the molecular weight of polypropylene carbonate is 280,000, and the molecular weight of polyvinyl butyral is 40,000.

[0123] (3) The slurry prepared in step (2) was dried at 50° C. in a vacuum atmosphere for 1 h to obtain a mixed powder.

[0124] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 5 g / cm 3 , and obtain a block with a thickness of 1 mm and an area of ​​2 cm 2 .

[0125] (5) The block prepared in step (4) is heated to 130°C at a heating rate of 10°C and degreased in a vacuum atmosphere for 90 minutes, and then heated to 1200°C at a heating rate of 10°C and sintered in a nitrogen atmosphere for 10 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0126] Embodiment 14

[0127] (1) Tantalum powder with a specific capacitance of 5000 μF·V / g and a purity of 99.95% is uniformly mixed with a dielectric material in a mass ratio of 70:30 to obtain tantalum powder coated with a dielectric material, wherein the dielectric material is a mixture of lead zirconate titanate and bismuth ferrite in a mass ratio of 1:1.

[0128] (2) 70% of dielectric material-coated tantalum powder, 9% of composite binder and 21% of N,N'-dimethylformamide were weighed and mixed evenly according to mass percentage to obtain a slurry, wherein the composite binder was methyl methacrylate and propylene carbonate mixed in a mass ratio of 2:1.

[0129] (3) Drying the slurry prepared in step (2) at 100° C. in a vacuum atmosphere for 20 min to obtain a mixed powder.

[0130] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 10 g / cm 3 , and obtain a block with a thickness of 2 mm and an area of ​​3 cm 2 .

[0131] (5) The block prepared in step (4) is heated to 250°C at a heating rate of 5°C and degreased in a nitrogen atmosphere for 50 minutes, and then heated to 2000°C at a heating rate of 5°C and sintered in a vacuum atmosphere for 10 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0132] Embodiment 15

[0133] (1) Tantalum powder with a specific capacitance of 5000 μF·V / g and a purity of 99.95% and bismuth ferrite with a particle size of 500 nm were uniformly mixed in a mass ratio of 70:30 to obtain dielectric material-coated tantalum powder.

[0134] (2) According to the mass percentage, 40% of tantalum powder coated with dielectric material, 0.1% of glycerol and 59.9% of methyl ethyl ketone were weighed and mixed evenly to obtain a slurry.

[0135] (3) Drying the slurry prepared in step (2) at 200° C. in a vacuum atmosphere for 20 min to obtain a mixed powder.

[0136] (4) The mixed powder prepared in step (3) is pressed into a block in a mold to a compacted density of 10 g / cm 3, and the block was obtained. The block thickness was 0.8 mm and the area was 2 cm 2 .

[0137] (5) The block prepared in step (4) is heated to 100° C. at a heating rate of 5° C. and degreased in an air atmosphere for 24 hours, and then heated to 1200° C. at a heating rate of 5° C. and sintered in a hydrogen atmosphere for 60 minutes to obtain a powder sintered tantalum electrolytic capacitor sintered block.

[0138] The powder sintered tantalum electrolytic capacitor sintered blocks prepared in Examples 1 to 6 of the present invention and Comparative Examples 1 to 2 were subjected to an energizing treatment, that is, a sintered powder sintered tantalum electrolytic capacitor anode was obtained by chemical treatment in a phosphoric acid system solution. Specifically, the chemical solution was a mixture of 2 volumes of 0.07 mol / L phosphoric acid aqueous solution and 1 volume of ethylene glycol in a volume ratio of 2:1, and then citric acid was added at 0.15 wt% of the total mass of the chemical solution. The chemical current density was 3 mAg -1 .

[0139] Table 1 Test results of sintered tantalum capacitor foil

[0140] experiment Capacitance (μF·V / g) <![CDATA[V f (V)]]> Example 1 7123 180 Comparative Example 1 6935 175 Example 2 45684 64 Comparative Example 2 42012 61 Example 3 7256 184 Example 4 7334 190 Example 5 46679 66 Example 6 47692 68

[0141] As can be seen from Table 1, compared with the electrostatic capacity and withstand voltage of the pure tantalum powder tantalum block anode in the comparative example, the electrostatic capacity and withstand voltage of the high dielectric constant tantalum block anode prepared by high dielectric constant coated tantalum powder in Examples 1-6 of the present invention are significantly improved, indicating that the introduction of dielectric substances, after high-temperature heat treatment and empowerment, effectively improves the dielectric constant of the block anode and inhibits the crystallization of tantalum pentoxide. When the crystallization phenomenon is serious, the dielectric layer is not dense and the withstand voltage performance is poor. The high dielectric constant tantalum block anode prepared by the gas phase coating method of Example 1 and Example 3 is significantly better than the high dielectric constant tantalum block anode prepared by mixing high dielectric constant powder, indicating that the high dielectric mixed layer prepared by the gas phase coating method is denser and the crystallization phenomenon of tantalum pentoxide is more obviously inhibited.

[0142] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0143] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing a powder sintered tantalum electrolytic capacitor anode, characterized in that: The following steps are involved: The tantalum powder is coated with a dielectric material to obtain tantalum powder coated with a dielectric material; the dielectric constant of the dielectric material is greater than the dielectric constant of tantalum pentoxide; The dielectric material is wrapped with tantalum powder, a binder and a solvent and mixed evenly to obtain a slurry, and the slurry is dried to remove the solvent to obtain a mixed powder; After the mixed powder block is shaped, it is degreased at 100°C to 550°C, and then sintered at 1200°C to 2000°C in an oxygen-free atmosphere. After the sintering is completed, it is energized to obtain a powder sintered tantalum electrolytic capacitor anode.

2. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The slurry is composed of the following components in percentage by mass: 40% to 80% of tantalum powder wrapped in dielectric material, 0.1% to 10% of binder, and the rest of solvent, which is 100% in total.

3. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The reaction time for degreasing is 10 minutes to 120 minutes.

4. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The sintering reaction time is 10 minutes to 120 minutes.

5. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The dielectric material is one or more of titanium dioxide, hafnium oxide, tantalum nitride, niobium oxide, barium titanate, strontium titanate, barium strontium titanate, lead zirconate titanate and bismuth ferrite.

6. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The specific capacitance of tantalum powder is 1000 μF·V / g to 150000 μF·V / g.

7. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The binder is one or more of polyvinyl alcohol, urea, polymethyl methacrylate, methyl methacrylate, polystyrene, polyvinyl chloride, stearic acid, glycerin, polyethylene glycol, paraffin, camphor, menthol, benzoic acid, polyethylene oxide, hydroxypropyl cellulose, acrylic resin, polypropylene carbonate, polyvinyl butyral and propylene carbonate.

8. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: During the briquetting step, the compaction density is 5g / cm 3 ~10g / cm 3 .

9. The method for preparing a powder sintered tantalum electrolytic capacitor anode according to claim 1, characterized in that: The coating method is liquid phase impregnation coating, vapor phase deposition coating or solid mixed coating.

10. A powder sintered tantalum electrolytic capacitor anode prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Solid electrolyte tantalum-niobium composite capacitor and preparation method thereof

    CN101859649A

  • A two-step method for manufacturing PEDT cathode plate tantalum electrolytic capacitors

    CN102270535A

  • Making method for anode body of electrolytic capacitor

    CN102842432A

  • Tantalum capacitor solid electrolyte and preparation method thereof, tantalum capacitor and electric appliance

    CN112038093A

  • Solid electrolyte material for tantalum capacitor lithium battery and preparation method of solid electrolyte material

    CN113488342A